“Nominal Trees” (нимтулописпу) in Microtoponymy of Udmurts - T. G. Vladykina; L. E. Kirillova (Научный диалог)
The names of certain trees in the local topography of the Udmurt Republic are discussed. The frequency of use of the names of the trees in the microtoponyms is revealed. The lexical-semantic types of microtoponymic names associating with everyday phenomena (activities of the inhabitants of a particular locus, events and experiences of certain people) or reflecting the links with the system of calendar and family rites are identified and analyzed. It is noted that “the names” of trees-characters as private manifestation of an archaic cult of trees marked the area, denoting sacred space of concrete calendar or family ritual, symbolized the centre of the Universe within a concrete locus. The authors give information that the villagers celebrated the coming of spring and the first out in the field ( гуджор , акашка ), summer peak ( гэршид / трочин¢ ) and summer end ( гэрбэр ) near such trees. The tree in the context of the rite also symbolized the natural stairs as one of the ways of ascension sacrifice to the gods. The tree marked the border of “alien” and “own” space: here one “met” relatives of groom, or “parted” (with a recruit). The recruiting rituals explicit mythological idea of a tree as the deputy of the human soul. The authors conclude that the most common for microtoponymy of Udmurt Republic are the names of the trees that retain echoes of pre-Christian religious beliefs associated with the notions of spirits - hosts of nature, most often about “the forest man” / “the forest owner” ( н ¢ улэсмурт ), gifts to him are usually presented under the fir tree ( њаз ¢ эг/с ¢ ийон ¢ н ¢ и ). The microtoponyms associated with the cult of ancestors are also of such frequency. The belief in the necessity of feeding the souls of the dead relatives, especially parents, are saved in the names of the trees that “took” a memorial sacrifice ( лы / куйан , йыр-пыд/с ¢ отон ). The microtoponyms given in the article are analyzed in the context of a mythological worldview and a broad typological correspondences with Slavic and other Finno-Ugric peoples.